2008
DOI: 10.1016/j.cca.2008.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Use of plasma DNA to predict mortality and need for intensive care in patients with abdominal pain

Abstract: Background:We investigated the value of plasma deoxyribonucleic acid concentrations in patients presenting with acute abdominal pain to predict need for intensive care or mortality. Methods: Plasma deoxyribonucleic acid taken from patients with acute abdominal pain was analyzed for the β-globin gene using the quantitative polymerase chain reaction. The primary outcome measure was the combined 28-day mortality or admission to the intensive care unit. Results: Of 287 consecutive patients with acute abdominal pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Also, the obtained results supported the applicability of plasma DNA estimation as predictor for prognosis of acute attacks as shown by Rainer et al (27) who studied patients with acute abdominal pain and found that median plasma DNA concentrations were three-fold higher in patients with systemic inflammatory response syndrome, five-fold higher in patients who died within 28 days, and eight-fold higher in patients admitted to ICU and concluded that plasma DNA may have a role in patients with acute abdominal pain as a marker for inflammation and cancer, and a predictor of ICU admission/mortality. Arnalich et al (28) studied 130 consecutive patients who underwent laparotomy for suspicious of acute mesenteric ischemia (AMI) and found that DNA concentration at admission was significantly higher in patients with AMI and in AMI patients who died compared to those with different diagnosis and concluded that plasma DNA levels may be a useful biomarker in predicting the outcome of patients with AMI.…”
Section: Results:-supporting
confidence: 84%
“…Also, the obtained results supported the applicability of plasma DNA estimation as predictor for prognosis of acute attacks as shown by Rainer et al (27) who studied patients with acute abdominal pain and found that median plasma DNA concentrations were three-fold higher in patients with systemic inflammatory response syndrome, five-fold higher in patients who died within 28 days, and eight-fold higher in patients admitted to ICU and concluded that plasma DNA may have a role in patients with acute abdominal pain as a marker for inflammation and cancer, and a predictor of ICU admission/mortality. Arnalich et al (28) studied 130 consecutive patients who underwent laparotomy for suspicious of acute mesenteric ischemia (AMI) and found that DNA concentration at admission was significantly higher in patients with AMI and in AMI patients who died compared to those with different diagnosis and concluded that plasma DNA levels may be a useful biomarker in predicting the outcome of patients with AMI.…”
Section: Results:-supporting
confidence: 84%
“…1), where 2710 studies by title and abstract screening were deemed irrelevant. Of the remaining 18 studies, six studies were excluded for the following reason: four studies were based on nontrauma patients [23–26] and two studies included both ICU and nonICU patients [27, 28]. A total of 15 studies from 14 references were included in this systematic review of which two studies were added after examining the included studies’ references lists (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with myocardial infarction (MI), the cf-DNA levels have been shown to correlate with traditional markers of myocardial damage, including creatine kinase (CK) and cardiac troponins, and to be associated with the post-infarction clinical course [3,4]. The results from two independent studies have also demonstrated that the cf-DNA levels in patients with acute coronary syndrome (ACS) correlate with the severity of the coronary artery lesions [5] and predict the 2-year mortality [6], thereby aiding the risk stratification of ACS. Although other studies did not observed such correlations, the authors nevertheless reported significantly elevated cf-DNA concentrations in MI patients and proposed that cf-DNA assessment could complement CK and troponin in a multimarker test format [7,8].…”
Section: Introductionmentioning
confidence: 95%